Teaching, research, and extension in current times: who challenges us? (Revista Científica Integrada, 2023)
In the field of Teaching, Research and Extension - pillars of the academy, there are countless challenges. To circumvent them, we need to go ahead exercising a culture of peace. In this editorial, I invite the readers of the Revista Científica Integrada (RCI) to explore with me the best ways to continue treading a journey towards quality education and science.
Keywords: Education; Research; Community-Institutional Relations